HSP90 inhibitor AUY922 induces cell death by disruption of the Bcr-Abl, Jak2 and HSP90 signaling network complex in leukemia cells - Tao, Wenjing (Impact Journals LLC, 2015)
The Bcr-Abl protein is an important client protein of heat shock protein 90 (HSP90). We evaluated the inhibitory effects of the HSP90 ATPase inhibitor AUY922 on 32D mouse hematopoietic cells expressing wild-type Bcr-Abl (b3a2, 32Dp210) and mutant Bcr-Abl imatinib (IM)-resistant cell lines. Western blotting results of fractions from gel filtration column chromatography of 32Dp210 cells showed that HSP90 together with Bcr-Abl, Jak2 Stat3 and several other proteins co-eluted in peak column fractions of a high molecular weight network complex (HMWNC). Co-IP results showed that HSP90 directly bound to Bcr-Abl, Jak2, Stat 3 and Akt. The associations between HSP90 and Bcr-Abl or Bcr-Abl kinase domain mutants (T315I and E255K) were interrupted by AUY922 treatment. Tyrosine phosphorylation of Bcr-Abl showed a dose-dependent decrease in 32Dp210T315I following AUY922 treatment for 16h. AUY922 also markedly inhibited cell proliferation of both IM-sensitive 32Dp210 (IC50 =6 nM) and IM-resistant 32Dp210T315I cells (IC50 ≈6 nM) and human KBM-5R/KBM-7R cell lines (IC50 =50 nM). AUY922 caused significant G1 arrest in 32Dp210 cells but not in T315I or E255K cells. AUY922 efficiently induced apoptosis in 32Dp210 (IC50 =10 nM) and T315I or E255K lines with IC50 around 20 to 50 nM. Our results showed that Bcr-Abl and Jak2 form HMWNC with HSP90 in CML cells. Inhibition of HSP90 by AUY922 disrupted the structure of HMWNC, leading to Bcr-Abl degradation, nhibiting cell proliferation and inducing apoptosis. Thus, inhibition of HSP90 is a powerful way to inhibit not only IM-sensitive CML cells but also IM-resistant CML cells.